2015
DOI: 10.5751/es-07532-200228
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating local institutions in irrigation experiments: evidence from rural communities in Pakistan

Abstract: ABSTRACT. Many irrigation systems are special cases of common-pool resources (CPRs) in which some users have preferential access to the resource, which in theory aggravates collective action challenges such as the under-provision of necessary infrastructure as a result of unequal appropriation of water resources. We present experimental evidence based on an irrigation game played in communities that are dependent on one of the largest contiguous irrigation network: the Indus basin irrigation system in Punjab, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, new frameworks to achieve consistency in agricultural production at the local level and in regions with similar socioeconomic conditions can be chalked out. As discussed by Javaid and Flak [62], up-to-date information via effective institutional support would lead to increased input use efficiency (irrigation water use efficiency in particular) among small-scale family farms. On the other hand, risk mitigation through insurance, forward contracting, and spreading sales are shown to promote resilience of farm families that indirectly affects sustainable agriculture [63].…”
Section: Perceived Risk Sources Mitigation Options and Implications For Sustainable Agriculturementioning
confidence: 99%
“…In addition, new frameworks to achieve consistency in agricultural production at the local level and in regions with similar socioeconomic conditions can be chalked out. As discussed by Javaid and Flak [62], up-to-date information via effective institutional support would lead to increased input use efficiency (irrigation water use efficiency in particular) among small-scale family farms. On the other hand, risk mitigation through insurance, forward contracting, and spreading sales are shown to promote resilience of farm families that indirectly affects sustainable agriculture [63].…”
Section: Perceived Risk Sources Mitigation Options and Implications For Sustainable Agriculturementioning
confidence: 99%
“…Players in our game were relatively cooperative, which is common in irrigation experiments (Janssen et al, 2011;Javaid and Falk, 2015). They also showed the commonly observed downward trend in investments over the rounds (Fehr and Gächter, 2000;Chaudhuri, 2011) even though it was not significant when controlling for the lag of other players' contributions.…”
Section: Discussionmentioning
confidence: 61%
“…An analysis of the discussion content shows that the players mainly used this opportunity to coordinate. They certainly also received signals about other's willingness to cooperate (Javaid and Falk, 2015;Balliet, 2010). The later effect was strengthened through the disclosure of everybody's contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Kreitmar (2015), public information about each user's extraction decisions led to higher levels of cooperation. Moreover, Javaid and Falk (2015) showed that external sanctions reduced the efficiency of group outcomes. Bell et al (2015) also performed irrigation experiments with farmers in Pakistan and included interactions between surface and groundwater supplies.…”
mentioning
confidence: 99%
“…One way to address this question is to run experiments in the field with nonstudent populations as participants. Javaid and Falk (2015) conducted irrigation dilemma experiments in irrigation communities in Pakistan. Consistent with Kreitmar (2015), public information about each user's extraction decisions led to higher levels of cooperation.…”
mentioning
confidence: 99%